PERLAKUAN AKUNTANSI PENDAPATAN DAN PENYAJIANNYA DALAM KEWAJARAN LAPORAN KEUANGAN PADA PT. ANDOWA NATHA WISTARA - Rosmawati; Budi Tri Rahardjo (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
The purpose of this study was to examine the accounting treatment of income and its presentation in the fairness of the financial statements at PT. Andowa Natha Wistara which is located at Sequis Center Building 4th Floor Jl. Jend. Sudirman Kav.71 South Jakarta 12190. The population of this study is the accounting treatment of PT. Andowa Natha Wistara. The sample of this research is the disclosure, measurement and recording at PT. Andowa Natha Wistara. The methods used by researchers in data collection are interviews, observations, and documentation. The technique used in this research is descriptive qualitative analysis. From this research the authors obtained the results that the accounting policy and recognition, and disclosure of measurements applied by PT. Andowa Natha Wistara complies with Statement of Financial Accounting Standards No. 23